20th century increase in body size of a hypoxia-tolerant bivalve documented by sediment cores from the northern Adriatic Sea (Gulf of Trieste). (October 2018) - Fuksi, Tomáš; Tomašových, Adam; Gallmetzer, Ivo; Haselmair, Alexandra; Zuschin, Martin
Abstract: An increase in the frequency of hypoxia, mucilages, and sediment pollution occurred in the 20th century in the Adriatic Sea. To assess the effects of these impacts on bivalves, we evaluate temporal changes in size structure of the opportunistic bivalve Corbula gibba in four sediment cores that cover the past 500 years in the northern, eutrophic part and 10, 000 years in the southern, mesotrophic part of the Gulf of Trieste. Assemblages exhibit a stable size structure during the highstand phase but shift to bimodal distributions and show a significant increase in the 95th percentile size during the 20th century. This increase in size by 2–3 mm is larger than the northward size increase associated with the transition from mesotrophic to eutrophic habitats. It coincides with increasing concentrations of total organic carbon and nitrogen, and can be related to enhanced food supply and by the tolerance of C. gibba to hypoxia. Highlights: Corbula gibba exhibited a stable size structure during the Holocene. An unprecedented increase in shell size occurred during the 20th century. This increase in shell size coincides with increasing concentrations of TOC.